DESIGN AND DEVELOPMENT OF NOVEL DRUG DELIVERY SYSTEM USING HERBAL MEDICINE TO TREAT ALZHEIMER’S DISEASE - RAMA RAO NADENDLA; LAKSHMI SWAPNA SAI; NIHITHA SANKA; SANTHI PRIYA NAGAM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study was focused to design an herbal formulation for the treatment of Alzheimer’s disease (AD) to develop the formulation using various techniques such as spray drying, centrifugation, and lyophilization and to conduct behavioral studies to evaluate the activity of the herbal formulation. Methods: Formulation contains herbal extracts such as curcumin, guggul, and ashwagandha. To develop this formulation, various techniques such as spray drying, centrifugation, and lyophilization were employed along with a natural polymer chitosan in various combinations of excipient. Preformulation studies such as solubility of herbal extracts and Fourier transmission infrared spectroscopy (FT-IR) studies for compatibility of the natural polymer with herbal extracts were studied. The formulation was characterized by tests such as particle size determination using optical microscopy, surface morphological evaluation using scanning electron microscopy (SEM), and behavioral testing by Morris water maze test using diazepam-induced amnesia method. Results: The particle size varied from 12.27 μ for normal chitosan to 3.59 μ for spray-dried chitosan. In the same way, the particle of normal formulation (12.9 μ) was about 4–5 times larger than that of spray-dried formulation (2.7 μ). The SEM images showed no proper morphology for chitosan, round surface with wrinkles for spray-dried chitosan, improper structures for normal formulation, and rounded smooth surface for spray-dried formulation. Significant p value was shown when the spray-dried test formulation was tested using diazepam-induced amnesia method. The transfer latency was noted on the 8th day and after 24 h of intraperitoneal administration of diazepam for the test group. Conclusion: In the present research study, an attempt was made to design and develop a novel drug delivery system using herbal medicine to treat AD. FT-IR compatibility study was carried out using the selected polymer and the herbal extracts using novel spray-drying techniques; behavioral studies were also done.